Sustainability of corporate based shallot farming business: Evidence from Malang Regency, Indonesia - Rita Parmawati; Rizha Hardyansah; Aditia Rahmawati (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
Shallot is the strategic horticulture commodity and one of superior national commodities. Ministry of Agriculture initiated a pilot project for the development of a corporate based shallot farming business area in Ngantang dan Pujon Districs, Malang Regency. This research aims to analyze the sustainability of the shallot farming in Ngantang and Pujon Districts, Malang Regency. Multidimensional Scaling (MDS) RAP-Shallot's analysis with five dimensions (ecological, economic, social, institutional, and technological) was used with a total of 49 attributes. The results of the sustainability index analysis show that the institutional, technological, and social dimensions are classified as quite sustainable, but the ecological and economic dimensions are still classified as less sustainable. Some attributes that are sensitive to the sustainability of shallot farming include integrated pest and disease control, marketing access of shallots, conflicts related to farming, the role of the middleman in harvest collecting, and the use of high quality and certified bulb. To improve the sustainability of shallot farming, the supervision and management of each attribute must be carried out optimally and integrated with many stakeholders such as farmers, traders, cooperatives, and the government.JEL Classification: Q01; Q02; Q20